2016
DOI: 10.1111/jog.13092
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of abnormal umbilical coiling according to a modified umbilical coiling index

Abstract: Umbilical coiling abnormalities were investigated using a novel umbilical venous coiling index. A hypocoiled umbilical cord evaluated by umbilical venous coiling index was found to be associated with fetal heart rate abnormalities, operative delivery, and nuchal cord entanglement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Ohno et al 17 reported that patients with umbilical cord torsion showed a significant decrease in the blood flow in the umbilical vein, which resulted in restricted fetal growth and various complications during delivery. In our study, the incidence of admission to the neonatal intensive care unit and the proportion of infants that were small for gestational age were significantly higher in patients with than without umbilical cord torsion, which is consistent with the results of the study by Ohno et al 17 This study has some limitations that should be acknowledged. We reviewed cases from a single hospital, and because of the retrospective nature of this study, some data may have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…Ohno et al 17 reported that patients with umbilical cord torsion showed a significant decrease in the blood flow in the umbilical vein, which resulted in restricted fetal growth and various complications during delivery. In our study, the incidence of admission to the neonatal intensive care unit and the proportion of infants that were small for gestational age were significantly higher in patients with than without umbilical cord torsion, which is consistent with the results of the study by Ohno et al 17 This study has some limitations that should be acknowledged. We reviewed cases from a single hospital, and because of the retrospective nature of this study, some data may have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the age of examining the UCI is different in numerous studies (11). Due to various reports on UCI, Ohno (19) pinpointed that coiling in umbilical vein and artery was not generally the same. Therefore, the UCI could not be sufficiently accurate for the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the degree of umbilical cord coiling are easy to screen for and have been linked to a number of adverse birth outcomes including prematurity, 1 spontaneous preterm delivery, 2 low birth weight (LBW), 1 small for gestational age (SGA) infants, [2][3][4][5] and nonreassuring fetal status. 1,[6][7][8][9][10] It has been proposed that cord coiling may be a result of hemodynamic stress 11,12 or external forces in utero such as nuchal cords, 13 fetal movement, 14,15 different umbilical vascular growth rates, 16 muscle fiber morphology, 17 or genetics. 18 The umbilical coiling index (UCI) is defined as the number of umbilical cord twists divided by the length of the cord in centimeters.…”
Section: Introductionmentioning
confidence: 99%
“…13,21 Other studies used their own distributions to classify <10th percentile as hypocoiling and >90th percentile as hypercoiling. 1,6,[8][9][10][22][23][24][25][26][27][28][29] Hypocoiling of the umbilical cord is commonly defined as a UCI < 10th percentile or less than 0.07 twists/cm. 19 The prevalence of hypocoiled cords in unselected singleton pregnancies ranges from 7.5% to 16.0% according to the previous literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation